Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat dalam Pelaksanaan Program Pelayanan Administrasi Terpadu Kecamatan (Paten) Di Kecamatan Nongsa Kota Batam - Juli Omar Sinaga; Rahmat Hidayat (Politeknik Negeri Batam, 2016)
he Sub-District Integrated Administrative Service (PATEN) is service implementation to the public in the sub-district, which its service procedure start from the submission of the application untill retrieval of completed documents, performed through only one service counter. The purpose of this research are, first to find out whether the variables of service quality (SERVQUAL) which consisting of five variables such as: tangible, reliability, responsiveness, assurance, and empathy has an influence of public's satisfaction; second to find out whether the five variables of service quality mentioned, simultaneously influence of public's satisfaction; third to find out which variable of service quality has the most dominant influence of public's satisfaction. The results of this research indicated, first from the five variables of service quality only tangible and empathy dimension influence of public's satisfaction; second service quality variable such as tangible, reliability, responsiveness, assurance, and empathy simultaneously influence of public's satisfaction; third the most dominant variable of the PATEN service quality influence of public’s satisfaction is empathy variable with the largest Beta value are 0.469 or 46,9 percent. To improve result quality of the research, conducted retesting regression with trimming models, retest the simultaneous significance (F statistical test) and partial regression.